PEMBENTUKAN KARAKTER RELIGIUS PADA SISWA MINU HIDAYATUN NAJAH TUBAN MELALUI SHOLAT BERJAMAAH - Fathul Amin (PREMIERE : Journal of Islamic Elementary Education, 2021)
The progress and development of science and technology at this time is indeed very rapid, social media is very easily accessible to all circles of society, including children. Then this affects moral changes in children, this is proven by the many phenomena of violations of laws, norms and values ​​committed by minors, this is more or less greatly influenced by the development of social media which is not balanced with moral education. The incident as described above is caused by several factors that influence the way of thinking of modern humans. Habituation of congregational midday and asr prayers for MINU Hidayatun Najah Tuban students is a top priority in efforts to build religious character This article uses this research using a case study method. In this study, researchers collected data from interviews with accompanying teachers, waka curriculum and principals. The conclusions that can be put forward are: 1. Religious character education through dzuhur and Asr prayers in congregation for MINU Hidayatun Najah students can be carried out optimally with commitment from various parties, both from students, accompanying teachers, curriculum waka, guardians of students and from the head of the madrasa. 2. The religious character that is formed through the dzuhur and asr prayers in congregation in MINU Hidayatun Najah students has 4 characteristics: 1) Maintaining cleanliness, 2) Discipline, 3) Unity and 4) Responsibility. 3. Shaping the character of students through the habit of praying dzuhur and asr in congregation can be carried out with an inclusive strategy. The inclusive strategy is a model of character education that is integrated into all the material presented in class subjects.